Large-Scale Learning for Local Change: The Challenge of Massive Open Online Courses as Educator Professional Learning - Littenberg-Tobias, Joshua; Slama, Rachel (Frontiers in Education, 2022)
How can large-scale open online learning serve the professional learning needs of educators which are often highly localized? In this mixed-methods study, we examine this question through studying the learning experiences of participants in four massive open online courses (MOOCs) that we developed on educational change leadership (N = 1,712). We observed that educators were able to integrate their learning from the online courses across a variety of educational settings. We argue that a key factor in this process was that the design of online courses was attentive to various levels in which participants processed and applied their learning. We therefore propose the “Content-Collaboration-Context Model” (C-C-C) as a design model for designing and researching open online learning experiences for professional learning settings where participants’ work is highly localized. In analyzing learner experiences in our MOOCs, we apply this model to illustrate how individuals integrated the de-contextualized content of the online courses into their context-specific practices. We conclude with implications for the design and research on open online professional learning experiences..